Synthesis, structure and properties of polyhydroxyalkanoates: biological polyesters - Sudesh, K; Abe, H; Doi, Y (Progress in polymer science, 2000)
High molecular weight polyhydroxyalkanoates (PHA) are synthesized and stored in the cell cytoplasm as water-insoluble inclusions by various microorganisms. This intriguing biological polyester initially attracted the attention of microbiologists and managed to keep many polymer scientists occupied over the second half of the last century. Concerted multidisciplinary scientific approaches have been directed to the elucidation of various aspects of PHA. Of significant interest are the findings that PHA can consist of various hydroxyalkanoate monomers, and the cloning of its biosynthesis genes. This has resulted in the production of PHA with various physical properties by genetically engineered microorganisms. In fact, it is now possible that large-scale production of PHA by transgenic plants can be achieved in the near future. The physical properties of PHA homopolymers as well as co- and heteropolymers have been the subject of study in various laboratories all over the world. By controlling the monomer composition of PHA, polymer scientists have shown that the polymer's physical properties can be regulated to a great extent. Furthermore, it is also clear that the rate of degradation of PHA in various environments can be controlled by judiciously altering its monomer compositions. This review attempts to bring together the biochemical and physicochemical aspects of PHA along with new perspectives on its potential therapeutic applications.